1987
DOI: 10.1093/nar/15.23.9909
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of the cytopathic effect of type A influenza viruses by oligodeoxynucleotides covalently linked to an intercalating agent

Abstract: Oligodeoxynucleotides covalently linked to an acridine derivative were targeted to part of the 3'-terminal sequence which is common to the eight RNAs of type A influenza viruses. The cytopathic effect of the virus on MDCK cells in culture was strongly decreased by a heptanucleotide covalently attached to the acridine ring. Control experiments using other oligonucleotide sequences showed that the effect was specific for the complementary sequence of the 3'-terminal region of the viral RNAs. The RNA transcriptas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 29 publications
0
55
1
Order By: Relevance
“…Antisense oligonucleotides complementary to viral RNA inhibit viral replication in cells cultured with Rous sarcoma virus [7], human irnmunodeficiency virus [8-lo], vesicular stomatitis virus [11,12], herpes simplex virus [11,14], and influenza virus [14,15]. However, the mechanism by which the antisense oligonucleotide inhibited retroviral protein synthesis, syncytia formation, and reverse transcriptase activity has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Antisense oligonucleotides complementary to viral RNA inhibit viral replication in cells cultured with Rous sarcoma virus [7], human irnmunodeficiency virus [8-lo], vesicular stomatitis virus [11,12], herpes simplex virus [11,14], and influenza virus [14,15]. However, the mechanism by which the antisense oligonucleotide inhibited retroviral protein synthesis, syncytia formation, and reverse transcriptase activity has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The viruses studied in this context include Rous sarcoma virus (1), simian virus (5), vesicular stomatitis virus (6,13), human immunodeficiency virus (HIV) (8)(9)(10)(11)(12), herpes simplex virus (7), and influenza virus (14).…”
mentioning
confidence: 99%
“…Acridinelinked oligonucleotides elicit RNase-H activity when bound to the complementary RNA sequence [20]. Moreover, it has been shown that such modified antisense oligomers can be used with intact cells, and prevent the development of the influenza virus [21] and of African trypanosomes in culture [14]. Our results indicate that they might also be of interest in the case of retroviruses.…”
Section: Resultsmentioning
confidence: 64%